1998
DOI: 10.3109/10611869808997876
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Targeting of Acoustically Reflective Immunoliposomes to Fibrin Under Various Flow Conditions

Abstract: We have previously demonstrated the development of acoustically reflective liposomes as a novel ultrasound contrast agent, that can be conjugated to antibodies for site specific acoustic enhancement of pathologically altered vascular tissue. The liposomes are echogenic due to the lipid composition, without gas entrapment, and have a size of less than one micron (Alkan-Onyuksel et al., 1996). When conjugated to anti-fibrinogen antibodies, the liposomes have the ability to attach to fibrin coated surfaces and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…We have performed previous experiments to demonstrate the link between Ab-labeled liposomes and fibrin using scanning electron microscopy (3). We have demonstrated in a flow chamber that 1) anti-fibrinogen conjugated liposomes retain their adherence to fibrin under physiologic sheer/flow (17) and 2) ELIPs retain their echogenic properties after 9 min of physiologic sheer (20). These studies provide evidence for ELIP targeting under physiologic conditions while retaining echogenic characteristics.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We have performed previous experiments to demonstrate the link between Ab-labeled liposomes and fibrin using scanning electron microscopy (3). We have demonstrated in a flow chamber that 1) anti-fibrinogen conjugated liposomes retain their adherence to fibrin under physiologic sheer/flow (17) and 2) ELIPs retain their echogenic properties after 9 min of physiologic sheer (20). These studies provide evidence for ELIP targeting under physiologic conditions while retaining echogenic characteristics.…”
Section: Discussionmentioning
confidence: 74%
“…Binding was specific, as it was Ͼ90% inhibited by the addition of soluble fibrinogen during Ab-ELIP incubation. Avidity and K assoc have been reported (15,17,18). We have demonstrated that the ELIP particle size after conjugation remained Ͻ1 m and, in most cases, remained between 500 and 800 nm (3).…”
Section: Methodsmentioning
confidence: 88%
“…Either the whole antibody or the variable Fab fragment of the mAb can be chemically conjugated to the surface of lipid nanocarriers to bring about increased cellular uptake at the targeted disease sites. We have previously conjugated antihuman fibrinogen and intercellular adhesion molecule (ICAM-1) antibodies onto acoustically reflective liposomes composed of phospholipids and cholesterol [110]. When injected into miniswine with plaque formation induced in the carotid and iliofemoral arteries, antifibrinogen conjugated liposomes were found to attach to thrombi and atheroma while anti-ICAM-1 conjugated liposomes attached to early atheroma, providing ultrasonic image enhancement of the targeted structures compared to unconjugated liposomes.…”
Section: Active Targetingmentioning
confidence: 97%
“…Monoclonal antibody (mAb) is another class of commonly used targeting moiety in drug delivery [23,109,110]. Either the whole antibody or the variable Fab fragment of the mAb can be chemically conjugated to the surface of lipid nanocarriers to bring about increased cellular uptake at the targeted disease sites.…”
Section: Active Targetingmentioning
confidence: 99%
“…ELIPs are composed of 4 primary lipids: PC, MPB-PE, PG, and cholesterol, and are made by a lyophilization process. 7,8,15 We have been able to quantitate the ELIP intravascular ultrasound enhancement of fibrin in vitro 9,18,19 and qualitatively demonstrate acoustic image enhancement of atheroma with anti-fibrinogen ELIPs delivered locally and imaged by transvascular and intravascular ultrasound. 10 Tiukinhoy et al 14 showed comparable echogenicity per particle of ELIPs compared with Albunex and other liposomal preparations.…”
Section: Discussionmentioning
confidence: 99%